Madrasah Diniyyah Takmiliyah: Pilar Pendidikan Karakter di Indonesia - Masduki Asbari (Yayasan Aya Sophia Indonesia, 2024)
Madrasah Diniyyah Takmiliyah has a significant role in shaping students' ethics, morals and attitudes at primary and secondary school levels. This research aims to explore the importance of education in Madrasah Diniyyah Takmiliyah in developing students' character. The research method used is qualitative with a case study approach in several madrasahs in Banten. The results showed that education in Madrasah Diniyyah Takmiliyah contributes significantly to the development of students' ethics, morals and attitudes. This research suggests that Madrasah Diniyyah Takmiliyah should be strengthened and supported by various parties to improve the quality of character education in Indonesia.